Key dimensions of collaboration quality in mental health care service networks. Issue 1 (2nd January 2021) - Nicaise, Pablo; Grard, Adeline; Leys, Mark; Van Audenhove, Chantal; Lorant, Vincent
ABSTRACT: Appropriate care delivery for patients with severe mental illness (SMI) requires a high level of collaboration quality between primary, mental health, and social care services. Few studies have addressed the interpersonal and inter-organizational components of collaboration within one unique study setting and it is unclear how these components contribute to overall collaboration quality. Using a comprehensive model that includes ten key indicators of collaboration in relation to both components, we evaluated how interpersonal and inter-organizational collaboration quality were associated in 19 networks that included 994 services across Belgium. Interpersonal collaboration was significantly higher than inter-organizational collaboration. Despite the internal consistency of the model, analysis showed that respondents perceived a conflict between client-centered care and leadership in the network. Our results reveal two approaches to collaborative service networks, one relying on interpersonal interactions and driven by client needs and another based on formalization and driven by governance procedures. The results reflect a lack of strategy on the part of network leaders for supporting client-centered care and hence, the persistence of the high level of fragmentation that networks were expected to address. Policy-makers should pay more attention to network formalization and governance mechanisms with a view to achieving effective client-centered outcomes.